The mobile marketing handbook : a step-by-step guide to creating dynamic mobile marketing campaigns - Dushinski, Kim, 1966- (Information Today, 2012)
"Focusing on the continuing integration of mobile marketing into the daily lives of consumers-locally, nationally, and globally-this updated second edition reflects the most current trends in mobile marketing and offers step-by-step guidelines to creating and maintaining successful mobile-marketing campaigns. Based on 20 years of experience in the field, this reference shows how this cost-effective strategy can be used successfully by businesses of any size and includes detailed information on legal implications and tracking, avoiding common mistakes, and the most current online resources for mobile marketers. The easy-to-follow tips on building stronger consumer relationships through apps and social networking will help any company put their message in the palms of customers' hands"--Vydavatelská anotace